Precipitation hardening martensitic stainless steel

A tailored precipitation hardening martensitic stainless steel with controlled element ratios and heat treatment achieves high strength and toughness at both room and low temperatures, addressing brittleness issues in conventional steels.

JP7615607B2Active Publication Date: 2025-01-17DAIDO STEEL CO LTD
View PDF 15 Cites 0 Cited by

Patent Information

Application Number
JP2020177624
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-02-04
Filing Date
2020-10-22
Publication Date
2025-01-17
Estimated Expiration
2040-10-22

AI Technical Summary

Technical Problem

Conventional precipitation hardening martensitic stainless steels become brittle at low temperatures, limiting their use in cold environments, and there is a lack of a steel that maintains high strength and toughness at both room and low temperatures.

Method used

A precipitation hardening martensitic stainless steel composition is developed with specific element ranges, including 0 < C < 0.10 mass%, 0 < Si ≤ 0.20 mass%, 0 < Mn ≤ 1.00 mass%, 8.0 ≤ Ni ≤ 15.0 mass%, 8.0 ≤ Cr ≤ 14.0 mass%, 0.10 ≤ Mo ≤ 3.0 mass%, and 0.4 ≤ Nb ≤ 2.50 mass%, with Fe and unavoidable impurities, and optimized heat treatment processes to enhance strength and toughness across temperature ranges.

Benefits of technology

The steel achieves high 0.2% yield strength of 1300 MPa or more at room temperature and absorbed energy of 30 J or more, with 10 J or more at -40°C, balancing strength and toughness across temperature variations.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007615607000001
    Figure 0007615607000001
  • Figure 0007615607000002
    Figure 0007615607000002
  • Figure 0007615607000003
    Figure 0007615607000003
Patent Text Reader

Abstract

To provide a precipitation-hardening martensitic stainless steel that is excellent in strength and toughness at room temperature and excellent in toughness at a low temperature.SOLUTION: The present invention relates to a precipitation-hardening martensitic stainless steel, containing: 0<C<0.10 mass%, 0<Si≤0.20 mass%, 0<Mn≤1.00 mass%, 8.0 mass%≤Ni≤15.0 mass%, 8.0 mass%≤Cr≤14.0 mass%, 0.4 mass%≤Nb≤2.50 mass%, and the balance being Fe and inevitable impurities. Preferably, the precipitation-hardening martensitic stainless steel further contains 0.10≤Al≤2.50 mass% and / or 0.10≤Ti≤1.50 mass%.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a precipitation hardening martensitic stainless steel, and more specifically to a precipitation hardening martensitic stainless steel excellent in strength and toughness at room temperature and in toughness at low temperatures. [Background technology]

[0002] Precipitation hardening stainless steel is a steel in which small amounts of Al, Cu, Mo, Ti, etc. are added to Cr-Ni stainless steel and intermetallic compounds are precipitated in the parent phase by heat treatment. Precipitation hardening stainless steel is classified into martensitic, semi-austenitic, and austenitic according to the structure of the parent phase. Among these, precipitation hardening martensitic stainless steels such as SUS630, PH13-8Mo, and Custom465 are used for aerospace structural components because of their excellent corrosion resistance, strength, and toughness.

[0003] Various proposals have been made regarding such precipitation hardened martensitic stainless steel. For example, Patent Document 1 discloses a precipitation hardening martensitic stainless steel in which intermetallic compounds are dispersed and precipitated, the martensitic stainless steel containing 0.1 mass % or less of C, 11 mass % to 13 mass % of Cr, 7.5 mass % to 11 mass % of Ni, 0.9 mass % to 1.7 mass % of Al, 0.85 mass % to 1.35 mass % of Mo, and 1.75 mass % to 2.75 mass % of W, with the balance being Fe and unavoidable impurities, and the Mo and W component amounts satisfying a predetermined relationship. The document describes that such precipitation hardened martensitic stainless steel has a high level of balance between mechanical strength and toughness, and also has excellent corrosion resistance.

[0004] Patent Document 2 discloses a precipitation-hardened martensitic stainless steel containing, by mass, C: 0.1% or less, Cr: 11-13%, Ni: 10.5-11.5%, Al: 0.25% or less, Ti: 0.9-1.5%, Mo+0.5W: 0.5-1.5%, Si: 1.0% or less, Mn: 1.0% or less, Mo / W (mass% ratio) 0.4-0.6, and the balance being iron and unavoidable impurities. The document describes that such precipitation-strengthened martensitic stainless steel has excellent structure stability, mechanical properties and corrosion resistance.

[0005] Patent Document 3 discloses a precipitation hardening martensitic stainless steel containing, by mass, 0.1% or less C, 0.1% or less N, 9.0% or more and 14.0% or less Cr, 9.0% or more and 14.0% or less Ni, 0.5% or more and 2.5% or less Mo, 0.5% or less Si, 1.0% or less Mn, 0.25% or more and 1.75% or less Ti, 0.25% or more and 1.75% or less Al, and the balance being Fe and unavoidable impurities. The document states that such precipitation hardened martensitic stainless steel is excellent in structure stability, strength, toughness and corrosion resistance, and does not require sub-zero treatment.

[0006] Patent Document 4 discloses a precipitation hardened martensitic stainless steel containing, by mass, 0.05% or less C, 0.05% or less N, 10.0% or more and 14.0% or less Cr, 8.5% or more and 11.5% or less Ni, 0.5% or more and 3.0% or less Mo, 1.5% or more and 2.0% or less Ti, 0.25% or more and 1.00% or less Al, 0.5% or less Si, 1.0% or less Mn, and the balance being Fe and unavoidable impurities. The document states that such precipitation hardened martensitic stainless steel is excellent in structure stability, strength, toughness and corrosion resistance, and does not require sub-zero treatment.

[0007] Patent Document 5 discloses a corrosion-resistant maraging alloy which is not a precipitation hardened martensitic stainless steel but contains 47.4 to 82.4 weight% Fe, 6 to 9 weight% Ni, 11 to 15 weight% Cr, 0.5 to 6 weight% Mo+1 / 2W, 0 to 6 weight% each of one or more of Co and Cu, 0 to 1 weight% each of one or more of Ti, Nb, Al, Si, Mn, V, 0 to 0.1 weight% each of one or more of rare earth elements or composite metals, 0 to 0.1 weight% C and N, and further contains 0.1 to 0.5 weight% Be. The document describes that such a corrosion-resistant maraging alloy can obtain a high hardness of 550 HV or more after age hardening while maintaining the existing corrosion resistance.

[0008] Furthermore, Patent Document 6 discloses a martensitic stainless steel having C: 0.15% or less (excluding 0), Si: 6.0% or less (excluding 0), Mn: 10.0% or less (excluding 0), Ni: 8.0% or less (excluding 0), Cr: 10.0 to 17.0%, N: 0.3% or less (excluding 0), Mo: 4.0% or less (including 0), Cu: 4.0% or less (including no addition), Co: 4.0% or less (including 0), with a Ni equivalent value in the range of 8.0 to 17.5, and the balance being Fe and unavoidable impurities. The document describes that the fatigue properties of such martensitic stainless steel can be improved by subjecting it to an appropriate heat treatment.

[0009] The characteristic of precipitation hardened martensitic stainless steel is that it obtains strength by dispersing fine precipitates. For example, PH13-8Mo obtains high strength and high toughness (toughness) by precipitating NiAl with Al as the strengthening element. Also, Custom465 obtains toughness by precipitating Ni3Ti with Ti as the strengthening element. However, conventional precipitation hardened martensitic stainless steels are embrittled at low temperatures, limiting their use at low temperatures, and there have been no examples of precipitation hardened martensitic stainless steels that exhibit high toughness even at low temperatures. [Prior art documents] [Patent documents]

[0010] [Patent Document 1] JP 2015-093991 A [Patent Document 2] JP 2014-201792 A [Patent Document 3] JP 2013-147698 A [Patent Document 4] JP 2013-001949 A [Patent Document 5] Japanese Patent Application Publication No. 09-143626 [Patent Document 6] Japanese Patent Application Publication No. 04-173926 Summary of the Invention [Problem to be solved by the invention]

[0011] An object of the present invention is to provide a precipitation hardening martensitic stainless steel that is excellent in strength and toughness at room temperature, and in toughness at low temperatures. [Means for solving the problem]

[0012] In order to solve the above problems, the precipitation hardening martensitic stainless steel according to the present invention comprises: 0 <C<0.10mass%、 0 <Si≦0.20mass%、 0 <Mn≦1.00mass%、 8.0≦Ni≦15.0mass%, 8.0≦Cr≦ 10.0 mass%, 0.10≦Mo≦3.0mass%, and Beauty, 0.4≦Nb≦2.50mass% The balance consists of Fe and unavoidable impurities. Effect of the Invention

[0013] In the past, Nb was rarely used as a strengthening element in precipitation hardening martensitic stainless steels. This is because the addition of Nb tends to produce harmful phases. However, when an appropriate amount of Nb is added as a strengthening element to precipitation hardening martensitic stainless steels and the stainless steels are heat treated under appropriate conditions, the stainless steels not only exhibit high strength and high toughness at room temperature, but also high toughness at low temperatures. When an appropriate amount of Nb is added and heat treatment is performed under appropriate conditions, Ni3Nb precipitates in the matrix. The appearance of high toughness at low temperatures is thought to be related to the shape of the precipitated Ni3Nb particles and the compatibility of the Ni3Nb particles with the matrix. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] An embodiment of the present invention will be described in detail below. [1. Precipitation hardening martensitic stainless steel] [1.1. Main constituent elements] The precipitation hardened martensitic stainless steel according to the present invention contains the following elements, with the balance being Fe and unavoidable impurities. The types of added elements, their component ranges, and the reasons for their limitations are as follows:

[0015] (1)0 <C<0.10mass%: C contributes to improving the strength of the base material by precipitating M2X type carbonitrides. C also contributes to refining the prior austenite grain size. To obtain such an effect, the C content must be more than 0 mass%. The C content is preferably 0.0005 mass% or more, and more preferably 0.0020 mass% or more. On the other hand, if the C content is excessive, a large amount of M2X carbonitrides will precipitate, and it will be necessary to increase the solution temperature. As a result, austenite grains will become coarse during solution formation, causing variations in properties. In addition, (Cr, Mo)-based carbides will precipitate excessively during aging treatment, reducing toughness and corrosion resistance. Furthermore, the martensitic transformation start temperature (Ms point) will decrease, stabilizing the austenite phase. Therefore, the C content must be less than 0.10 mass%. The C content is preferably 0.05 mass% or less, more preferably 0.01 mass% or less.

[0016] (2)0 <Si≦0.20mass%: Silicon acts as a deoxidizer. If the amount of silicon is too small, deoxidation during melting is insufficient, and the cleanliness is reduced. Therefore, the amount of silicon must be more than 0 mass%. The amount of silicon is preferably 0.005 mass% or more. On the other hand, if the amount of Si is excessive, oxide-based inclusions are formed and the toughness is reduced. Therefore, the amount of Si must be 0.20 mass% or less. The amount of Si is preferably 0.15 mass% or less, and more preferably 0.10 mass% or less.

[0017] (3)0 <Mn≦1.00mass%: Mn has the effect of suppressing the grain boundary segregation of S, which is mixed in as an impurity. In order to obtain such an effect, the Mn content must be more than 0 mass%. The Mn content is preferably 0.005 mass% or more. On the other hand, if the Mn content is excessive, sulfides increase and toughness decreases. Also, the Ms point decreases and the austenite phase is stabilized. Therefore, the Mn content must be 1.00 mass% or less. The Mn content is preferably 0.50 mass% or less, and more preferably 0.20 mass% or less.

[0018] (4) 8.0≦Ni≦15.0mass%: Ni is an important element that precipitates intermetallic compound phases such as NiAl and Ni3(Al,Ti) and contributes to improving the strength of the base material. Ni also has the effect of suppressing the formation of δ-ferrite phase. Furthermore, Ni lowers the ductile-brittle transition temperature (DBTT) of the base phase and contributes to improving toughness at room temperature. In order to obtain such effects, the Ni content must be 8.0 mass% or more. The Ni content is preferably 9.0 mass% or more, and more preferably 10.0 mass% or more. On the other hand, if the Ni content is excessive, the Ms point decreases. As a result, the amount of retained austenite increases and the strength decreases. Therefore, the Ni content must be 15.0 mass% or less. The Ni content is preferably 13.5 mass% or less, and more preferably 13.0 mass% or less.

[0019] (5) 8.0≦Cr≦14.0mass%: Cr contributes to adjusting the Ms point, and the lower the Cr content, the higher the Ms point. Therefore, the lower the Cr content, the less retained austenite there is after solution treatment or subzero treatment. This also improves the homogeneity of the microstructure and increases the 0.2% yield strength. On the other hand, Cr is an element necessary for ensuring corrosion resistance. If the Cr content is low, coarser M than M2X type carbonitrides are formed. 23 C6 carbides are stabilized, and the 0.2% proof stress decreases. Therefore, the Cr content must be 8.0 mass% or more. The Cr content is preferably 8.5 mass% or more.

[0020] On the other hand, the more the Cr content, the lower the Ms point. Therefore, if the Cr content is excessive, the amount of retained austenite before aging treatment becomes excessive, and the 0.2% yield strength decreases. Furthermore, if the Cr content is excessive, the δ ferrite phase is easily formed. Therefore, the Cr content must be 14.0 mass% or less. The Cr content is preferably 12.0 mass% or less, and more preferably 10.0 mass% or less.

[0021] (6) 0.4≦Nb≦2.50mass%: Nb precipitates rod-shaped Ni3Nb particles with a width of 2 to 20 nm and a length of several tens of nm, which contributes to improving the strength of the base material. In addition, when Al or Ti is added to the steel, that is, when the steel contains intermetallic compounds such as NiAl or Ni3(Al,Ti), Nb forms Ni(Al,Nb) or Ni3(Al,Ti,Nb) in which part of the Al or Ti in NiAl or Ni3(Al,Ti) is replaced by Nb, and is used to improve the strength of the base material. Furthermore, Nb forms carbonitrides and contributes to refining the crystal grains. In order to obtain such an effect, the Nb content must be 0.4 mass% or more, preferably 0.50 mass% or more, and more preferably 0.60 mass% or more.

[0022] On the other hand, if the Nb content is excessive, the precipitation strengthening phase and inclusion carbon increase, and the toughness decreases. Also, if the Nb content is excessive, the δ ferrite phase is easily formed. Therefore, the Nb content must be 2.50 mass% or less. The Nb content is preferably 1.50 mass% or less, and more preferably 1.00 mass% or less.

[0023] (7) Inevitable impurities: In the present invention, the term "unavoidable impurities" refers to trace components that are mixed in from raw materials or refractories during the production of stainless steel. Specific examples of inevitable impurities include the following: (a)P≦0.050mass%: P reduces the toughness and ductility of steel. It also reduces hot workability due to grain boundary segregation. However, if the P content is 0.050 mass% or less, the adverse effects are small.

[0024] (b) S≦0.050mass%: S reduces the toughness and ductility of steel. In addition, S reduces hot workability due to grain boundary segregation. Furthermore, S combines with Ti to form sulfide-based inclusions. However, as long as the S content is 0.050 mass% or less, the adverse effects are small.

[0025] (c) N≦0.050mass%: N forms nitrides and reduces toughness and ductility. N also lowers the Ms point and stabilizes the austenite phase. However, if the N content is 0.050 mass% or less, the adverse effects are small. The N content is preferably 0.03 mass% or less, and more preferably 0.01 mass% or less.

[0026] (d) O≦0.010mass%: O forms oxide inclusions and reduces toughness, but as long as the O content is 0.010 mass% or less, the adverse effects are minimal.

[0027] (e) Al<0.10mass%: (f) Ti<0.10mass%: As described later, Al and Ti are elements that precipitate intermetallic compounds and contribute to improving the strength of the base material, but they can also be mixed in as unavoidable impurities. When controlled as unavoidable impurities, Al and Ti are each limited to less than 0.10 mass%. When controlled as unavoidable impurities, there is no need to set a lower limit, and the lower limit is 0 mass% for both.

[0028] (g) Cu<0.30mass%: A trace amount of Cu has the effect of improving strength without significantly impairing toughness, while an excessive amount of Cu may reduce toughness and hot workability. Therefore, the upper limit of Cu is limited to less than 0.30 mass%, preferably less than 0.10 mass%. Cu may be mixed in as an unavoidable impurity, but there is no need to set a lower limit, which is 0 mass%.

[0029] (h) Mo<0.10mass%: (i) W<0.10mass%: (j) Co<0.10mass%: (k)V<0.30mass%: As described later, Mo, W, Co, and V are elements that contribute to improving the strength of the base material, but they can also be mixed in as unavoidable impurities. When controlled as unavoidable impurities, Mo, W, Co, and V are limited to less than the above-mentioned values. When controlled as unavoidable impurities, there is no need to set a lower limit, and the lower limit is 0 mass% for each.

[0030] [1.2. Sub-constituent elements] The precipitation hardened martensitic stainless steel according to the present invention may further contain one or more of the following elements in addition to the elements described above. The types of added elements, their component ranges, and the reasons for their limitations are as follows:

[0031] (8) 0.10≦Al≦2.50mass%: Al forms an intermetallic compound (spherical NiAl of 2 to 20 nm) with Ni, and contributes to improving the strength of the base material. Al also functions as a deoxidizing element. To obtain such an effect, the Al content can be 0.10 mass% or more. It is preferably 0.30 mass% or more, more preferably 0.50 mass% or more, and even more preferably 0.70 mass% or more. On the other hand, if the Al content is excessive, the precipitation strengthening phase and inclusions increase, and the toughness decreases. Also, if the Al content is excessive, the δ ferrite phase is easily formed. Therefore, the Al content is preferably 2.50 mass% or less. The Al content is preferably 2.00 mass% or less, and more preferably 1.50 mass% or less.

[0032] (9) 0.10≦Ti≦1.50 mass% : Like Al, Ti forms intermetallic compounds with Ni (rod-shaped Ni3Ti with a width of 2 to 20 nm and a length of several tens of nm) and contributes to improving the strength of the base material. As a result, the grain boundary strength is improved, which contributes to improving toughness. Furthermore, Ti forms carbonitrides and contributes to refining crystal grains. To obtain such effects, the Ti content is preferably 0.10 mass% or more. On the other hand, if the Ti content is excessive, the precipitation strengthening phase and inclusions increase, and the toughness decreases. Also, if the Ti content is excessive, the δ ferrite phase is easily formed. Therefore, the Ti content is preferably 1.50 mass% or less. The Ti content is preferably 1.30 mass% or less, and more preferably 1.10 mass% or less.

[0033] Either Ti or Al may be added, or both may be added. However, when the Al content is 0.10 mass% or more and 2.50 mass%, the Ti content is preferably less than 0.10 mass%. This is because the Ni(Al, Nb)-based intermetallic compound is more effective in improving strength without impairing toughness than the Ni(Ti, Nb)-based intermetallic compound.

[0034] (10) 0.10≦Co≦10.0mass%: Co has the effect of promoting the precipitation of fine precipitates that affect strength. To obtain such an effect, the Co content is preferably 0.10 mass% or more. The Co content is preferably 3.0 mass% or more, and more preferably 6.0 mass% or more. On the other hand, if the amount of Co is excessive, the cost increases. Therefore, the amount of Co is preferably 10.0 mass% or less. The amount of Co is preferably 9.0 mass% or less, and more preferably 8.0 mass% or less.

[0035] (11) 0.10≦Mo≦3.0mass%: Mo precipitates M2X type carbonitrides and contributes to improving the strength of the base material. Mo also contributes to refining the prior austenite grain size. Furthermore, Mo contributes to improving the strength, toughness, and corrosion resistance. To obtain such effects, the Mo content is preferably 0.10 mass% or more. The Mo content is preferably 0.3 mass% or more, and more preferably 0.5 mass% or more. On the other hand, if the Mo content is excessive, a large amount of M2X type carbonitrides are precipitated, and it becomes necessary to raise the solution temperature. Therefore, the austenite grains become coarse during solution formation, which causes characteristic variations. Furthermore, if the Mo content is excessive, the δ ferrite phase is easily formed. Therefore, the Mo content is preferably 3.0 mass% or less. The Mo content is preferably 2.5 mass% or less, and more preferably 2.0 mass% or less.

[0036] (12) 0.10≦W≦3.0mass%: W precipitates M2X type carbonitrides and contributes to improving the strength of the base material. W also contributes to refining the prior austenite grain size. Furthermore, W contributes to improving the strength, toughness, and corrosion resistance. To obtain such effects, the W content is preferably 0.10 mass% or more. The W content is preferably 0.3 mass% or more, and more preferably 0.5 mass% or more. On the other hand, if the W content is excessive, a large amount of M2X type carbonitrides are precipitated, and it becomes necessary to increase the solution temperature. Therefore, austenite grains become coarse during solution formation, which causes characteristic variations. Furthermore, if the W content is excessive, the δ ferrite phase is easily formed. Therefore, the W content is preferably 3.0 mass% or less. The W content is preferably 2.5 mass% or less, and more preferably 2.0 mass% or less.

[0037] (13) 0.3≦V≦2.0mass%: When Al or Ti is added to steel, that is, when steel contains intermetallic compounds such as NiAl or Ni3(Al,Ti), V contributes to improving the strength of the base material by forming Ni(Al,V) or Ni3(Al,Ti,V) in which part of the Al or Ti in NiAl or Ni3(Al,Ti) is replaced by V. Furthermore, V forms carbonitrides and contributes to refining the crystal grains. In order to obtain such an effect, the V content is preferably 0.3 mass % or more.

[0038] On the other hand, if the V content is excessive, the precipitation strengthening phase and inclusion carbon increase, and the toughness decreases. Also, if the V content is excessive, the δ ferrite phase is easily formed. Therefore, the V content is preferably 2.0 mass% or less. The V content is preferably 1.5 mass% or less, and more preferably 1.0 mass% or less.

[0039] (14) 0.01≦Ta≦1.0mass%: When Al or Ti is added to steel, that is, when steel contains intermetallic compounds such as NiAl or Ni3(Al,Ti), Ta forms Ni(Al,Ta) or Ni3(Al,Ti,Ta) in which part of the Al or Ti in NiAl or Ni3(Al,Ti) is replaced by Ta, and is used to improve the strength of the base material. Furthermore, Ta forms carbonitrides and contributes to the refinement of crystal grains. In order to obtain such an effect, the Ta content is preferably 0.01 mass % or more.

[0040] On the other hand, if the Ta content is excessive, the precipitation strengthening phase and inclusion carbon increase, which reduces the toughness. Also, if the Ta content is excessive, the δ ferrite phase is easily formed. Therefore, the Ta content is preferably 1.0 mass% or less.

[0041] (15) 0.0001≦B≦0.0100mass%: B increases grain boundary strength and contributes to improving toughness. To obtain such an effect, the B content is preferably 0.0001 mass% or more. The B content is preferably 0.0005 mass% or more, and more preferably 0.0010 mass% or more. On the other hand, if the B content is excessive, a large amount of BN is formed, which reduces toughness. Therefore, the B content is preferably 0.0100 mass% or less. The B content is preferably 0.0050 mass% or less, and more preferably 0.0030 mass% or less.

[0042] (16)0.0001≦Ca≦0.0100mass%: Ca has the effect of refining carbides and oxides and refining crystal grains, thereby contributing to improving toughness. In order to obtain such effects, the Ca content is preferably 0.0001 mass% or more. On the other hand, if the Ca content is excessive, the hot workability is deteriorated. Therefore, the Ca content is preferably 0.0100 mass% or less. The Ca content is preferably 0.0050 mass% or less.

[0043] (17)0.0001≦Mg≦0.0100mass%: Mg has the effect of refining carbides and oxides and refining crystal grains, thereby contributing to improving toughness. In order to obtain such effects, the Mg content is preferably 0.0001 mass% or more. On the other hand, if the Mg content is excessive, the hot workability is deteriorated. Therefore, the Mg content is preferably 0.0100 mass% or less, and more preferably 0.0050 mass% or less.

[0044] (18) 0.001≦Zr≦0.050mass%: Zr has the effect of refining carbides and oxides and refining crystal grains, thereby contributing to improving toughness. In order to obtain such effects, the Zr content is preferably 0.001 mass% or more. On the other hand, if the Zr content is excessive, the hot workability is deteriorated. Therefore, the Mg content is preferably 0.050 mass% or less. The Zr content is preferably 0.030 mass% or less.

[0045] (19) 0.001≦REM≦0.050mass%: REM has the effect of refining carbides and oxides and refining crystal grains, thereby contributing to improving toughness. In order to obtain such effects, the REM content is preferably 0.001 mass% or more. On the other hand, if the REM content is excessive, the hot workability is deteriorated. Therefore, the REM content is preferably 0.050 mass% or less, and more preferably 0.030 mass% or less.

[0046] [1.3. Characteristics] [1.3.1. 0.2% proof stress] The precipitation hardened martensitic stainless steel according to the present invention exhibits a relatively high 0.2% yield strength when its components are optimized and it is subjected to an appropriate heat treatment. Specifically, by optimizing the components and heat treatment conditions, the 0.2% yield strength at room temperature becomes 1300 MPa or more. By further optimizing the components and heat treatment conditions, the 0.2% yield strength at room temperature becomes 1400 MPa or more.

[0047] [1.3.2. Absorbed energy] The precipitation hardened martensitic stainless steel according to the present invention exhibits a relatively high absorbed energy when its components are optimized and it is subjected to an appropriate heat treatment. Specifically, by optimizing the components and heat treatment conditions, the absorbed energy at room temperature is 30 J or more. By further optimizing the components and heat treatment conditions, the absorbed energy at room temperature is 50 J or more. Furthermore, by optimizing the components and heat treatment conditions, the absorbed energy at -40°C becomes 10 J or more. By further optimizing the components and heat treatment conditions, the absorbed energy at -40°C becomes 20 J or more.

[0048] [2. Manufacturing method of precipitation hardened martensitic stainless steel] The precipitation hardening martensitic stainless steel according to the present invention is (a) Melting and casting raw materials mixed to obtain a desired composition; (b) subjecting the resulting ingot to a homogenization heat treatment; (c) The material after the homogenization heat treatment is hot forged, (d) The hot forged material is subjected to solution heat treatment, (e) After solution heat treatment, the material is subjected to sub-zero treatment as necessary. (f) Aging treatment is performed on materials after solution heat treatment or sub-zero treatment. It can be produced by the above method.

[0049] [2.1. Melting and casting process] First, the raw materials mixed to obtain a desired composition are melted and cast. The method and conditions for melting and casting are not particularly limited, and the most suitable method and conditions can be selected depending on the purpose.

[0050] [2.2. Homogenization heat treatment process] Next, the obtained ingot is subjected to a homogenization heat treatment. The homogenization heat treatment is performed to remove segregation that occurs during casting. The conditions of the homogenization heat treatment are not particularly limited as long as such an effect is achieved. Usually, the homogenization heat treatment is performed by heating and holding the ingot under the conditions of a temperature of 1150 to 1240°C and a time of 10 hours or more.

[0051] [2.3. Hot forging process] Next, the material after the homogenization heat treatment is hot forged. Hot forging is performed to destroy the coarse cast structure and to refine the structure. The conditions of hot forging are not particularly limited as long as such effects are achieved. Usually, hot forging is performed by heating the material under conditions of 700 to 1240 ° C. × 1 hr or more, forging under conditions of a forging end temperature of 700 ° C., and then air cooling. Note that hot forging may be performed continuously after the homogenization heat treatment without cooling the material to room temperature.

[0052] [2.4. Solution heat treatment process] Next, the material after hot forging is subjected to solution heat treatment. The solution heat treatment is performed to transform the material into austenite single phase and then into martensite. The conditions of the solution heat treatment are not particularly limited as long as such effects are achieved. Usually, the solution heat treatment is performed by heating the material under the conditions of temperature: 800 to 1200°C x heating time: 1 to 10 hours and cooling it. Examples of cooling methods include air cooling, air blast cooling, oil cooling, and water cooling.

[0053] [2.5. Sub-zero treatment process] Next, the material after the solution heat treatment is subjected to sub-zero treatment as necessary. The sub-zero treatment is performed to transform the austenite remaining after the solution heat treatment into martensite. The conditions of the sub-zero treatment are not particularly limited as long as such an effect is achieved. Usually, the sub-zero treatment is performed by holding the material at a temperature of 0°C or less for 1 to 10 hours.

[0054] [2.6. Aging treatment process] Next, the material after the solution heat treatment or the subzero treatment is subjected to an aging treatment. The aging treatment is performed to precipitate intermetallic compound phases such as B2 phase and η phase in the parent phase. The conditions of the aging treatment are not particularly limited as long as such effects are achieved. Usually, the aging treatment is performed by heating the material at 400 to 600°C for 1 to 24 hours. After the heat treatment, the material is cooled by air cooling.

[0055] [3. Effect] Precipitation hardened martensitic stainless steel has the property of being embrittled at low temperatures while having excellent toughness at room temperature. Therefore, it was difficult for conventional precipitation hardened martensitic stainless steel to simultaneously satisfy the conditions of 0.2% proof stress of 1300 MPa or more at room temperature, absorbed energy of 30 J or more at room temperature, and absorbed energy of 10 J or more at low temperature (-40°C). For this reason, austenitic stainless steel, which has excellent toughness at low temperatures, is generally used for components used in low-temperature environments. However, austenitic stainless steel has inferior strength and toughness at room temperature compared to precipitation-hardened martensitic stainless steel, which has imposed design limitations.

[0056] In contrast, Nb has not been used much as a strengthening element in precipitation hardening martensitic stainless steels in the past because the addition of Nb tends to produce harmful phases. However, when an appropriate amount of Nb is added to precipitation hardening martensitic stainless steels as a strengthening element and the stainless steels are heat treated under appropriate conditions, the stainless steels not only exhibit high strength and toughness at room temperature, but also show high toughness at low temperatures. When an appropriate amount of Nb is added and heat treatment is performed under appropriate conditions, Ni3Nb precipitates in the matrix. The appearance of high toughness at low temperatures is thought to be related to the shape of the precipitated Ni3Nb particles and the compatibility of the Ni3Nb particles with the matrix.

[0057] Furthermore, when Al and / or Ti are added in combination with Nb, the strength and toughness at room temperature, as well as the toughness at low temperatures, are further improved. Furthermore, when Co is added in addition to Nb, the strength and toughness at room temperature can be further improved. This is believed to be because the addition of Co promotes the precipitation of strengthening phases. Therefore, the precipitation hardening martensitic stainless steel according to the present invention has the following properties: (a) 0.2% proof stress (@room temperature) ≧1300MPa, (b) Absorbed energy (at room temperature) ≧ 30 J, and (c) Absorbed energy (@-40℃) ≧ 10J It is possible to simultaneously satisfy the above requirements. EXAMPLES

[0058] ( Examples 1 to 8, Reference Examples 9 to 10, Examples 11 to 21, Reference Examples 22 to 23, Examples 24 to 25, Reference Examples 26 to 27, Examples 28 to 36 , Comparative Examples 1 to 10) [1. Sample preparation] 50 kg of steel having the composition shown in Tables 1 and 2 was melted in a vacuum induction furnace and cast into an ingot. Then, homogenization heat treatment was performed at 1200°C for 24 hours with air cooling. Furthermore, a round bar of φ24 mm was forged under the conditions of a starting temperature of 1200°C and a final temperature of 900°C, and then air cooled. Next, each steel ingot was subjected to solution heat treatment at 1000℃ for 1 hour with water cooling, followed by sub-zero treatment at -76℃ for 6 hours, and then aging treatment at 530℃ for 4 hours with air cooling.

[0059] [Table 1]

[0060] [Table 2]

[0061] 2. Test Method [2.1. Tensile test (measurement of 0.2% yield strength)] A tensile test was carried out in accordance with the metal tensile test method specified in ASTM A370 to measure the 0.2% yield strength. The test temperature was room temperature. [2.2. Charpy impact test] A 2 mm V-notch test piece was taken so that the longitudinal direction coincided with the forging direction. Using this test piece, impact properties (absorbed energy) were measured in accordance with the ASTM A370 standard. The test temperature was room temperature or -40°C.

[0062] [3. Results] The results are shown in Table 3. From Table 3, the following can be seen. Regarding the 0.2% yield strength (@RT) in Table 3, "A" indicates that the 0.2% yield strength is 1400 MPa or more, "B" indicates that the 0.2% yield strength is 1300 MPa or more and less than 1400 MPa, and "C" indicates that the 0.2% yield strength is less than 1300 MPa. Regarding the absorbed energy (@RT), "A" indicates that the absorbed energy (@RT) is 60J or more, "B" indicates that the absorbed energy (@RT) is 40J or more but less than 60J, and "C" indicates that the absorbed energy (@RT) is less than 40J. Furthermore, with regard to the absorbed energy (@-40℃), "A" indicates that the absorbed energy (@-40℃) is 20J or more, "B" indicates that the absorbed energy (@-40℃) is 10J or more but less than 20J, and "C" indicates that the absorbed energy (@-40℃) is less than 10J.

[0063] (1) Comparative Example 1 has low absorbed energy at room temperature and at −40° C. This is believed to be due to an excess of Si. (2) Comparative Example 2 has low absorbed energy at room temperature and at −40° C. This is believed to be due to the small amount of Ni. (3) Comparative Example 3 has a low 0.2% proof stress at room temperature. This is believed to be due to an excess of Ni. (4) Comparative Example 4 has a low 0.2% proof stress at room temperature. This is believed to be due to the low Cr content. (5) Comparative Example 5 has low absorbed energy at room temperature and at −40° C. This is believed to be due to an excess of Cr.

[0064] (6) Comparative Example 6 has low absorbed energy at room temperature and at −40° C. This is believed to be due to the excess Mo. (7) Comparative Example 7 has low absorbed energy at room temperature and at −40° C. This is believed to be due to an excess of Al. (8) Comparative Example 8 has low absorbed energy at room temperature and at −40° C. This is believed to be due to an excess of Ti. (9) Comparative Example 9 has low absorbed energy at room temperature and at −40° C. This is believed to be due to the small amount of Nb. (10) Comparative Example 10 has low absorbed energy at room temperature and at −40° C. This is believed to be due to the excess Nb.

[0065] (11) Examples 1 to 8, Reference Examples 9 to 10, Examples 11 to 21, Reference Examples 22 to 23, Examples 24 to 25, Reference Examples 26 to 27, Examples 28 to 36 Both of these materials have high 0.2% proof stress at room temperature and also high absorbed energy at room temperature and at -40°C.

[0066] [Table 3]

[0067] Although the embodiment of the present invention has been described in detail above, the present invention is not limited to the above embodiment, and various modifications are possible without departing from the gist of the present invention. [Industrial Applicability]

[0068] The precipitation hardening martensitic stainless steel according to the present invention is (a) A rotor and a stator of a mud motor component in an underground drill, which rotates due to hydraulic force from a fluid. (b) A drive shaft that transmits the rotation of the rotor and stator; (c) a structural member of the bearing that holds the drive shaft; (d) Structural components of measurement-while-drilling tools (MWD) that measure the drilling depth, inclination, and azimuth of the drill string of an underground drill; (e) Logging-while-drilling tools (LWD) structural components for geological analysis; (f) MWD and LWD housing materials, It can be used as: Other applications include steam turbine blades, aerospace structural components, and high-strength fasteners.

Claims

1. 0<C<0.10mass%, 0<Si≦0.20mass%, 0<Mn≦1.00mass%, 8.0≦Ni≦15.0mass%, 8.0≦Cr≦10.0mass%, 0.10≦Mo≦3.0 mass%, and 0.4≦Nb≦2.50mass% and the balance being Fe and unavoidable impurities.

2. 0.10≦Al≦2.50 mass%, or 0.10≦Ti≦1.50mass% The precipitation hardening martensitic stainless steel according to claim 1 , further comprising:

3. 0.10≦Al≦2.50 mass%, and 0.10≦Ti≦1.50mass% The precipitation hardening martensitic stainless steel according to claim 1 , further comprising:

4. 0.10≦Co≦10.0mass% The precipitation hardening martensitic stainless steel according to any one of claims 1 to 3, further comprising:

5. 0.10≦W≦3.0mass%, 0.3≦V≦2.0mass%, 0.01≦Ta≦1.0 mass%, 0.0001≦B≦0.0100mass%, 0.0001≦Ca≦0.0100 mass%, 0.0001≦Mg≦0.0100mass%, 0.001≦Zr≦0.050 mass%, and 0.001≦REM≦0.050mass% The precipitation hardening martensitic stainless steel according to any one of claims 1 to 4, further comprising one or more selected from the group consisting of:

Citation Information

Patent Citations

  • Enclosed motor compressor

    JP1984074380A

  • Precipitation hardening high tensile stainless steel having excellent welding strength and toughness

    JP1989025952A

  • Production of precipitation hardening type high tensile stainless steel excellent in welding strength and toughness

    JP1990190416A

  • Stainless steel having excellent strength, spring properties and formability

    JP1990225649A

  • Method for providing fatigue characteristic to martensitic stainless steel strip

    JP1992173926A